FRACTURES OF THE TIBIAL PILON - HORIZONTAL ARTICULAR SURFACE OF THE TIBIA - Bryam Esteban Coello García,; Dubal Wladimir Fernández Ordoñez,; Alba Estefanía Iza Román,; Leyda Coralía Loor Martínez,; Marlon Leonardo Ordóñez Ramos,; José Luis Granizo Jara,; Edgar Gabriel Pesántez Bravo,; Daniela Lorena Barros Narváez,; Mishell Estefanía Peñafiel Vicuña,; Bonny María Montalván Nivicela10, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Introduction: The distal tibia presents a quadrilateral cross-sectional shape and together with the fibula, ligaments and capsule, create the ankle mortise. The tibial pilon fractures thus to describe the high energy axial compressive force of the tibia when it acts as a mortar and is placed vertically on the talus. Objective: to detail current information related to tibial pilon fractures, epidemiology, mechanism of action, clinical assessment, imaging assessment, classification, treatment, prognosis and complications. Methodology: a total of 28 articles were analyzed in this review, including review and original articles, as well as clinical cases, of which 19 bibliographies were used because the other articles were not relevant to this study. The sources of information were PubMed, Google Scholar and Cochrane; the terms used to search for information in Spanish, Portuguese and English were: distal tibia fractures, horizontal articular surface of the tibia, tibial pylon, arthrodesis. Results: tibial pilon fractures account for 7% to 10% of all tibial fractures, are more common in males aged 30 to 40 years and the vast majority are associated with high-energy trauma. Conclusions: Individuals presenting with high-energy pylon fractures may also have multisystem trauma and other potentially life-threatening alterations. Imaging evaluation is important for good preoperative planning, as well as for scheduling a strategic reconstruction order. The prognosis of the fractured individual correlates with the type of fracture according to the Rüedi and Allgöwer classification which is based on the severity of comminution and displacement of the articular surface. Treatment is based on several factors, among which are the individual's age and functional status, the severity of the bone, cartilage and soft tissue injury, the degree of comminution and osteoporosis, as well as the surgeon's skill. Few authors recommend arthrodesis in acute fracture. Even when a precise reduction is achieved, good results are not always obtained. Without anatomic reduction, the results are not satisfactory. Clinical outcomes correlate with the severity of the fracture pattern as well as the quality of the reduction.